Characteristics of the Manifestation of Psychological Health in Adolescence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article covers the issues of psychological characteristics of the manifestation of psychological health in adolescence. Initially, opinions were put forward regarding the main features of the development of psychological health in adolescence. At the same time, from an empirical point of view, aspects of the interrelationship of individual methods of psychological health in adolescence were analyzed.